The 25th hour - Benioff, David (Plume, 2002)
All Monty Brogan ever wanted was to be a fireman. Now he's just got 24 hours before he will start a seven-year stretch in the federal penitentiary for drug dealing. As the minutes count down, Monty seizes one last chance to stack the odds in his favor.